1993
DOI: 10.1136/hrt.70.1.98-a
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and the heart

Abstract: Pronounced episodic oxygen desaturation in the postoperative period: its association with ventilatory pattern and analgesic regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…As a typical example of adaptive evolution in extreme environments ( Richalet, 2007 ), high-altitude acclimatization refers to the heritable and irreversible changes in morphology ( Brutsaert et al, 1999 ; Miles et al, 2009 ), physiology ( Storz et al, 2009 ; Naeije, 2010 ), biochemistry ( García-Hjarles, 1989 ; Li et al, 2010 ), and ethology ( Mamatov et al, 2012 ) in highland habitants during long-term selection pressure, such as reduced oxygen availability, low ambient temperatures, and high ultraviolet radiation (UV; Brookfield and Allen, 1989 ; Wang et al, 2014 ). These changes are primarily triggered on a molecular level to modulate organic metabolism, especially in representatively hypoxia-sensitive tissues such as heart ( Jarmakani et al, 1978 ; Wilson et al, 1993 ; Moromisato et al, 1996 ; Park et al, 2007 ; Chen et al, 2009 ), kidney ( Luks et al, 2008 ; Dan et al, 2010 ; Yijiang et al, 2013 ), liver ( Komolova and Egorov, 1985 ; Moromisato et al, 1996 ; Rong and Gastroenterology, 2009 ), lung ( Moromisato et al, 1996 ; Liu, 2011 ; Li et al, 2012 ), longissimus muscle ( Lundby et al, 2003 , 2009 ; Murray, 2009 ; Levett et al, 2012 ; Zhang et al, 2015 ), and spleen ( Ou et al, 1980 ; Kam et al, 1999 ; Richardson et al, 2008 ). Previous studies reported sufficient evidence for a molecular genetic basis of high-elevation acclimatization ( Breen et al, 2008 ; Simonson et al, 2010 ; Scott et al, 2011 ; Bigham et al, 2013 ; Yang et al, 2017 ), and genomic patterns of genetic variation among populations and species have been widely elucidated in recent years ( Cheviron and Brumfield, 2012 ; Mingzhou et al, 2013 ; Qu et al, 2013 ; Ai et al, 2014 ; Zhou et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a typical example of adaptive evolution in extreme environments ( Richalet, 2007 ), high-altitude acclimatization refers to the heritable and irreversible changes in morphology ( Brutsaert et al, 1999 ; Miles et al, 2009 ), physiology ( Storz et al, 2009 ; Naeije, 2010 ), biochemistry ( García-Hjarles, 1989 ; Li et al, 2010 ), and ethology ( Mamatov et al, 2012 ) in highland habitants during long-term selection pressure, such as reduced oxygen availability, low ambient temperatures, and high ultraviolet radiation (UV; Brookfield and Allen, 1989 ; Wang et al, 2014 ). These changes are primarily triggered on a molecular level to modulate organic metabolism, especially in representatively hypoxia-sensitive tissues such as heart ( Jarmakani et al, 1978 ; Wilson et al, 1993 ; Moromisato et al, 1996 ; Park et al, 2007 ; Chen et al, 2009 ), kidney ( Luks et al, 2008 ; Dan et al, 2010 ; Yijiang et al, 2013 ), liver ( Komolova and Egorov, 1985 ; Moromisato et al, 1996 ; Rong and Gastroenterology, 2009 ), lung ( Moromisato et al, 1996 ; Liu, 2011 ; Li et al, 2012 ), longissimus muscle ( Lundby et al, 2003 , 2009 ; Murray, 2009 ; Levett et al, 2012 ; Zhang et al, 2015 ), and spleen ( Ou et al, 1980 ; Kam et al, 1999 ; Richardson et al, 2008 ). Previous studies reported sufficient evidence for a molecular genetic basis of high-elevation acclimatization ( Breen et al, 2008 ; Simonson et al, 2010 ; Scott et al, 2011 ; Bigham et al, 2013 ; Yang et al, 2017 ), and genomic patterns of genetic variation among populations and species have been widely elucidated in recent years ( Cheviron and Brumfield, 2012 ; Mingzhou et al, 2013 ; Qu et al, 2013 ; Ai et al, 2014 ; Zhou et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…If local tissue hypoxia can lead to systemic hypoxaemia is the converse the case: that systemic hypoxaemia can cause local tissue hypoxia? Some studies have found a link between systemic hypoxaemia and myocardial ischaemia (Wilson & Reilly, 1993) but others dispute this link (Entwhistle et al. , 1994; Smith et al.…”
Section: Introductionmentioning
confidence: 99%